MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI LOGIKA MATEMATIKA DENGAN PENDEKATAN PROBLEM BASED LEARNING (PBL) SISWA KELAS XI - Rifan Alamsah; Wahyu Setiawan (IKIP Siliwangi, 2022)
This research is classroom action research (classroom action research). This research was conducted on class XI OTKP-2 SMK TI Garuda Nusantara in the academic year 2021-2022 with a total of 15 students. The purpose of this research is to find out the use of Problem Based Learning approach in the learning process to improve student learning outcomes in mathematical logic subjects. Data collection techniques are carried out by means of observation, documentation and test questions. The steps of Classroom Action Research are 2 cycles by doing a pre-cycle (before the action), doing worksheets, and finally giving a final test (after giving the action). Data processing in this study using excel. The results of this study indicate that the Problem Based Learning approach can improve student learning outcomes in class XI OTKP-2 SMK TI Garuda Nusantara with the acquisition of grades in cycle 1 as many as 4 students (26.67%) increasing in cycle 2 or final test as many as 13 students ( 86.66%). It can be concluded that the Problem Based Learning approach can improve student learning outcomes in the material of mathematical logic for class XI.